The Role of Autophagy in Sepsis: Protection and Injury to Organs - Yin, Xin; Xin, Huang; Mao, Shuai; Wu, Guangping; Guo, Liheng (Frontiers in Physiology, 2019)
Sepsis is a systemic inflammatory disease with infection, and autophagy has been shown to play an important role in sepsis. This review summarizes the main regulatory mechanisms of autophagy in sepsis and its latest research. Recent studies have shown that autophagy can regulate innate immune processes and acquired immune processes, and the regulation of autophagy in different immune cells is different. Mitochondrial autophagy can select damaged mitochondria and remove it to deal with oxidative stress damage. The process of mitochondrial autophagy is regulated by other factors. Non-coding RNA is also an important factor in the regulation of autophagy. In addition, more and more studies in recent years have shown that autophagy plays different roles in different organs. It tends to be protective in the lungs, heart, kidneys, and brain, and tends to be damaging in skeletal muscle. We also mentioned some drugs that can regulate autophagy. The process of modulating autophagy through drug intervention appears to be a new potential hope for the treatment of sepsis.